Risk preference and child labor: Econometric evidence - Raymond Boadi Frempong; David Stadelmann (Review of Development Economics, 2021)
Households may invest in the human capital development of their children not only for altruistic reasons but also as insurance against future income shocks. Therefore, the allocation of the child's time between school and work is a function of the risk preference of the household head. This paper analyzes the relationship between parental risk preferences and child labor decisions using recall information on child labor and a risk elicitation question. Results reveal that risk-averse households are more likely to send their children to work. Endogeneity issues are addressed by employing instrumental variables. These results suggest that child labor may be driven by the need to maximize the household's expected income from the child. Regarding heterogeneity, we find that the child labor effect of risk-aversion is higher for older children. Furthermore, the father's risk-aversion matters for the probability of child labor, while the intensity of child labor increases with the mother's risk-aversion. The findings call for an understanding of the behavioral context of the affected households and how risk preferences can affect the success of proposed policies to reduce child labor.
Keywords: 330; altruism; child labor; household welfare; human capital; risk preference; uncertainties